Profile of investigative capacities that determine factors to investigate in the universities of Peru - Sánchez Castro, Angélica (2022)
The need to develop research in the Peruvian university context is urgently needed. That is why, in order to develop the research processes, it is required to have a profile of the research capacity of the students. For this reason, the purpose was to determine the profile of investigative capacities that derive from factors to investigate in universities. It corresponds to the quantitative approach, of a transversal type; a sample made up of 303 university students was used. Two instruments were used: investigative skills scale and the questionnaire of factors that influence investigative skills with construct validity by the KMO test (0.623 and 0.706,respectively). The results referring to the profiles showed that 32.3% of the respondents identified themselves with the reflective inquiry investigative capacity profile, followed by 26.7% with the generic conceptualization investigative capacity profile; while 27.7% were related to the specific cognitive investigative abilities profile and, finally, 13.2% ofthose evaluated were identified in the active cognitive construction investigative abilities profile. It is concluded that students have investigative skills at different progressive levels, with different characteristics depending on the influence of factors in the training process.